The phonomenom of youth gangs in dosquebradas, linked to a bulk crisis of meaning (2020)
This article analyzes the processes of socialization, taking up the theory of Social Construction of Reality by Berger and Luckman. This is articulated with the theory of Amalio Blanco groups in order to account for the operation of gangs in the city of Dosquebradas and the implications for young people who are part of these groups. We conclude that gangs act as groups make sense of life and sense of belonging to those who choose to integrate. An interview was conducted with the Magistrate Zapata Eisenhower's interest supplement existing information on the operation of gangs in Pereira and Dosquebradas.